Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1469-8137.1998.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of leaf surface contamination in beech, oak, and ginkgo in relation to leaf micromorphology and wettability

Abstract: The leaf surfaces of beech, oak and ginkgo have been investigated with respect to contamination with particles during one growing season. Based on the observation that particles are removed from water-repellent leaves by rain (Lotus effect) the three species were selected because they differ in leaf surface micromorphology and wettability. Leaves of beech are smooth, lacked wax crystals and were pwettable. Those of ginkgo were rough because their cells were convex and were densely covered by wax crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(142 citation statements)
references
References 28 publications
5
129
0
1
Order By: Relevance
“…Because the leaf is the main agent of ambient particle entrapment by plants [37], Chai et al [38] tested leaves and found that roughness and density of villi as adhesion points affect particle detention. Neinhuis [39] proved by research that particle detention ability of easily-wet leaves is strong, while those with special surface structures and hydrophobic wax are not readily wetted and also have poor particle detention ability. Tomasevic et al [40; using SEM-EDAX] studied particles on leaves of horse chestnut (Aesculus hippocastanum) and Turkish hazel (Corylus colurna).…”
Section: Particle Absorption and Species Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the leaf is the main agent of ambient particle entrapment by plants [37], Chai et al [38] tested leaves and found that roughness and density of villi as adhesion points affect particle detention. Neinhuis [39] proved by research that particle detention ability of easily-wet leaves is strong, while those with special surface structures and hydrophobic wax are not readily wetted and also have poor particle detention ability. Tomasevic et al [40; using SEM-EDAX] studied particles on leaves of horse chestnut (Aesculus hippocastanum) and Turkish hazel (Corylus colurna).…”
Section: Particle Absorption and Species Variationmentioning
confidence: 99%
“…Hwang et al [4] chose five tree species to perform a chamber experiment whose results show that the intercept potential of conifers is higher than that of broadleaf trees. Neinhuis et al [24] have proposed that Ginkgo biloba has "self-cleaning" characteristics, so its particle retention ability is poor [25].…”
Section: Introductionmentioning
confidence: 99%
“…Wetting of leaf surfaces can be analysed quantitatively by measuring contact angles of aqueous solutions on leaf surfaces (Holloway, 1969(Holloway, , 1970. The influence of the chemical wax composition (Holloway, 1969) and of environmental factors on contact angles has been extensively studied (Cape, 1983 ;Turunen & Huttunen, 1990, Percy & Baker, 1991Cape & Percy, 1993 ;Brewer & Smith, 1997 ;Neinhuis & Barthlott, 1998). However, little information exists about the influence of epiphytic micro-organisms on leaf-surface wetting (Bunster, Fokkema & Schippers, 1989).…”
Section: mentioning
confidence: 99%
“…The CAs of Nelumbo nucifera and Colocasia esculenta were significantly lower than 90° when the wax was removed with acetone from the leaf surface by Burton and Bhushan (2006). Neinhuis and Barthlott (1998) demonstrated that high CAs (130°-140°) for Ginkgo biloba leaves can be attributed to the density of wax crystals covering the leaf during the whole period of growth, while leaves of Quercus robur, which are only partially covered by amorphous wax, have hydrophobic properties only a few weeks after the wax crystals were produced. Therefore, our findings of different CA values between the five groups and between species within the same plant family could be related to differences in cuticular wax content between species and during different leaf developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemistry of cuticular wax (e.g., wax content, composition and microstructure) affects the leaf surface wettability (Neinhuis and Barthlott 1998;Wang et al 2015). The cuticular waxes vary considerably between and among different species.…”
Section: Discussionmentioning
confidence: 99%